Strategi Pembelajaran Adaptif untuk Anak Usia Dini dengan Gaya Belajar Visual (Studi Kasus Tunggal) di TK Dharma Wanita I Jember - Ulul Azmi Hoiriyah; Hisbiyatul Hasanah; Ianatuz Zahro (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
This study aims to analyze adaptive learning strategies for early childhood learners with visual learning styles through a single case study conducted at TK Dharma Wanita I Jember. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data analysis followed the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing. The findings indicate that visual strategies, such as the use of images, colors, and videos, effectively support children’s understanding of learning materials in accordance with their learning styles. These strategies may serve as a reference for designing adaptive learning practices in early childhood education. The novelty of this study lies in the contextual identification of adaptive learning strategies specifically designed for early childhood learners with visual learning styles. The results support responsive learning strategies that are aligned with the differentiation approach promoted in the Merdeka Curriculum.